We the children - Clements, Andrew, 1949-2019.; Stower, Adam (New York : Atheneum Books for Young Readers, 2010)
Sixth-grader Ben Pratt's life is full of changes that he does not like--his parents' separation and the plan to demolish his seaside school to build an amusement park--but when the school janitor gives him a tarnished coin with some old engravings and then dies, Ben is drawn into an effort to keep the school from being destroyed.
A Junior Library Guild selection
Ages 7-10.
Keywords: Mystery and detective stories; Schools -- Fiction; Sailing -- Fiction; Schools -- Juvenile fiction; Sailing -- Juvenile fiction